Indagine sull’interazione Crassostrea gigas – OsHV-1 μvar in un allevamento in ambiente lagunare del Mediterraneo centro-occidentale - CIVETTINI M; SABA S; PINNA MG; GORLA A; MAGNABOSCO C; ZAMBON M; PRETTO T; ARCANGELI G.; PAIS, Antonio (2012)
Aim of this work was to monitor the presence of OsHV-1 μvar in a farm of C. gigas in lagoon environment in order to test the interaction with environmental parameters. The virus has been found in association with mortality and temperature rise, although in the months before the oysters were negative.